2011
DOI: 10.1007/s12640-011-9260-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Alleviates ADHD Symptoms: Regional Deficits and Development Trajectory

Abstract: The heterogeneous, chronic, and proliferating aspect of attention deficit hyperactivity disorder (ADHD) and comorbidities covers heritability, cognitive, emotional, motor, and everyday behavioral domains that place individuals presenting the condition at some considerable disadvantage. Disruption of "typical developmental trajectories" in the manifestation of gene-environment interactive predispositions implies that ADHD children and adolescents may continue to perform at defective levels as adults with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 201 publications
(170 reference statements)
2
59
0
1
Order By: Relevance
“…Although most studies of exercise in children have focused on typically-developing youth, the areas of cognition that were found to be improved mainly included those related to executive functioning and the activation of prefrontal cortex, and thus are highly relevant to ADHD. While some attention has been paid to the impact of acute physical activity on ADHD symptoms [63], and investigators have pointed out the theoretical potential of chronic physical exercise in ADHD [64,65], randomized controlled trials of physical exercise as a treatment for ADHD have yet to be published.…”
Section: Physical Exercisementioning
confidence: 99%
“…Although most studies of exercise in children have focused on typically-developing youth, the areas of cognition that were found to be improved mainly included those related to executive functioning and the activation of prefrontal cortex, and thus are highly relevant to ADHD. While some attention has been paid to the impact of acute physical activity on ADHD symptoms [63], and investigators have pointed out the theoretical potential of chronic physical exercise in ADHD [64,65], randomized controlled trials of physical exercise as a treatment for ADHD have yet to be published.…”
Section: Physical Exercisementioning
confidence: 99%
“…Estudos apresentam a atividade física como auxiliar no tratamento do TDAH (GAPIN; LABBAN; ETNIER, 2011;VERRET et al, 2012;ARCHER;KOSTRZEWA, 2012;MAO et al, 2014;HALPERIN;BERWID;O'NEILL, 2014). Em especial, Gapin, Labban e Etnier, em 2011, evidenciam que a atividade física proporciona efeitos benéficos sobre o desempenho cognitivo, bem como na gestão de sintomas comportamentais e melhoria do desempenho cognitivo de crianças com TDAH.…”
Section: Discussionunclassified
“…Both human and animal studies strongly support the impact of exercise on improved cognitive function [83]. Exercise has been found to improve executive function and increase prefrontal activation during executive function tasks in children [84•], and some initial work has documented that exercise in children with ADHD has yielded improvements in overall behavior, sustained attention, vigilance, and impulsivity [85,86].…”
Section: Exercisementioning
confidence: 99%
“…Exercise has been found to improve executive function and increase prefrontal activation during executive function tasks in children [84•], and some initial work has documented that exercise in children with ADHD has yielded improvements in overall behavior, sustained attention, vigilance, and impulsivity [85,86]. Exercise increases brain-derived neurotrophic factor, a molecule involved in synaptic plasticity, learning, and memory, which may be particularly important for individuals with ADHD [83]. Additionally, Gapin et al [87] reported some preliminary, albeit indirect, evidence that exercise increases dopamine levels in children with ADHD [87].…”
Section: Exercisementioning
confidence: 99%